The Influence of Work Environment and K3 on Employee Productivity in the Production Division at Companies in Tangerang Regency - Popong Suryani; Agung Abdul Mulik (LPPM STIE PPI, 2024)
Introduction/Main Objectives: To determine the influence of the Work Environment and K3 on Employee Productivity in the production department of a plastic company in Tangerang Regency. Background Problems: Failure to achieve production targets and high reject products are suspected to be due to the company's physical environment and lack of sensitivity to awareness of the Health and Safety of all employees in the production department. Novelty: Re-testing previous research at different research locations and sample types. Research Methods: Using a descriptive quantitative method with a quantitative approach based on the philosophy of positivism, on 34 Respondents with SPSS as an analysis tool. Finding/Results: There is a significant influence between the Work Environment and K3 on Productivity, both partially and simultaneously. Conclusion: Improving existing facilities in the company to create a comfortable work environment and always using PPE while working, this requires strict supervision from several supervisors in the work area.